The Indicative System of Assessing the Level of Ecologization in the Context of the Region’s Sustainable Development - Rudneva, Larissa N.; Pchelintseva, Irina G.; Guryeva, Maria A. (International Journal of Economics and Financial Issues, 2016)
The article over views the evolution of the term “ecologization” and provides the authors’ interpretation; it discusses basic aspects of creating the indicative system of assessing the level of ecologization of the region’s economy as an element of assessingthe region’s sustainable development. The dependence obtained by the authors enables one to easily determine the state of the region’s ecologization. The analysis provides the possibility to track the progress of both positive and negative changes. The ranges of integrated indicators will signal about the qualitative condition of the level of ecologization of the region. If there are negative tendencies, regional development programs require revision in order to improve the situation and reach the reference value of the indicator. Keywords: Ecologization; economy ecologization; assessing the region’s sustainable development; the indicative system of assessing ecologization; the level of ecologization of the region’s economy. JEL Classifications: Q01; Q5